Buckling Analysis of Steel Semi-Spherical Shells with Square Cutout under Axial Compression - Torabi, H.; Shariati, M. (Проблемы прочности, 2014)
Buckling of steel thin walled semi-spherical shells with square cutout due to axial compressive loads has been studied by numerical simulations, and results were compared with those from the experiments.